CONTROLLING IN CHINESE COMPANIES: A FIRST PEEK BEHIND THE BAMBOO CURTAIN - Rickards, Robert C.; Kong, Jing; Ritsert, Rolf (The International Journal of Accounting and Business Society, 2014)
Curiously, neither investigators inside the PRC nor researchers outside it previously have undertaken largescale, systematic, empirical study of Chinese companies’ controlling behavior. The dearth of such studies is particularly surprising given the remarkable growth of business in China during the past thirty years, Chinese companies’ emphasis on low costs, and the determination of the country’s leadership to see it move up the value chain during its next phase of economic development – all areas where controlling should have a major role to play. This paper reports fist responses from a portion of an ongoing, online survey about current controlling practices in a broad cross-section of Chinese industries. It thus offers unique initial insights into such areas as: personnel responsible for controlling and their qualifiations;kinds of planning practiced and the effort involved; and the differing foci of various planning types.Keywords: budgeting, Chinese enterprises, controlling, forecasting, management accounting, planning